Records of the hermit crab genus Pagurixus Melin, 1939 (Crustacea: Decapoda: Anomura: Paguridae) from Europa Island, western Indian Ocean, with descriptions of two new species - Komai, Tomoyuki; Poupin, Joseph (Zootaxa, 2013)
Three species of the pagurid hermit crab genus Pagurixus Melin, 1939, are reported from Europa Island in the Mozambique Strait, western Indian Ocean: P. haigae Komai & Osawa, 2007, P. annulus n. sp., and P. europa n. sp. Pagurixus haigae is recorded from the western Indian Ocean for the first time. Pagurixus annulus n. sp. and P. europa n. sp. are referred to the P. boninensis (Melin, 1939) species group and P. anceps (Forest, 1954) group, respectively. Diagnostic characters of these two new species are discussed.